2018
DOI: 10.3855/jidc.9774
|View full text |Cite
|
Sign up to set email alerts
|

Field accuracy of HIV rapid diagnostic tests for blood donors screening, Bukavu, Eastern Democratic Republic of the Congo

Abstract: Introduction: Rapid diagnostic tests (RDTs) are widely used for point-of-care diagnosis of HIV infection in resource-limited settings. However, there are no data about their field diagnostic performance in Eastern Democratic Republic of the Congo (DRC), especially in the context of blood banks screening for transfusion safety purpose. Methodology: Blood specimens were collected from blood donors in Bukavu, Eastern DRC, from May the 1 st to June the 30 th , 2015, to evaluate the accuracy of Alere Determine HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…21 The study is consistent with the ndings by Kashosi who found that when compared to the laboratorybased ELISA HIV Ag/Ab assay, the currently used 3rd generation HIV RDTs showed poor eld accuracy. 17 According to their Manufacturers, RDTs have high sensitivity and speci city for licensing purposes and subsequent World Health Organization (WHO) prequali cation. 18 Despite this, HIV RDTs have some limitations since they cannot identify persons who are within the window period of an acute HIV infection because these individuals have not yet developed HIV-speci c antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…21 The study is consistent with the ndings by Kashosi who found that when compared to the laboratorybased ELISA HIV Ag/Ab assay, the currently used 3rd generation HIV RDTs showed poor eld accuracy. 17 According to their Manufacturers, RDTs have high sensitivity and speci city for licensing purposes and subsequent World Health Organization (WHO) prequali cation. 18 Despite this, HIV RDTs have some limitations since they cannot identify persons who are within the window period of an acute HIV infection because these individuals have not yet developed HIV-speci c antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 This study highlights the important issue of possible false-negative HIV test results, which in part may be explained by the failure of these RDTs to diagnose HIV during the window. 17 During this period, HIV infection can be detected only by tests detecting also viral antigen such as the laboratory-based 4th generation ELISA. 22 The baseline HIV prevalence in the population in uences the negative and PPV and needs to be considered in the interpretation of HIV RDT results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations